Derivational Processes: Underlying Forms and Analogies in Ḥayyûjs Linguistic Works - Kaplan, Roger Jay (AJS review, 1995)
This study examines Rabbi Yehuda Hayyûj′s (945-1000 C.E.) use of two derivational processes: underlying forms and linguistic analogies (singular: Arabic Hebrew ), which were an integral element of his work. Since his goal was to show the derivation of Hebrew verbs from triliteral roots, he focused on weak verbs whose surface forms did not demonstrate all three radicals. He compared many weak verbs to other verbal forms in order to identify the exact inflection of words, especially their verbal pattern and consonantal roots.